OVERVIEW ON GENERICS POLICIES AND PHARMACEUTICAL PRICING IN THE EUROPEAN COUNTRIES AND THE REPUBLIC OF MACEDONIA - Merita Dauti; Edita Alili- Idrizi; Sihana Ahmeti-Lika; Ledjan Malaj (European Scientific Journal, ESJ, 2015)
Continued growth of spending on drugs in Health care, especially in the public sector encouraged initiatives for reforms in the system of determining the prices of medicines. These initiatives that were undertaken, were primarily aimed at reducing the cost of drugs but parallel to become a generic medications simultaneously promoting an adjustment of reimbursement procedures in the pharmaceutical sector. The policies for the regulation of the pharmaceutical market come as a response to health care classical market failures. This article will focus on the features, implementation and impact of these policies in some EU member states. Most EU countries, apply the external reference system of prices, whereupon the price of a certain medication is determined based on the price of the same product in other countries. On the other hand, in twenty other EU member states, prices are determined by comparing the prices of the same products according to chemical, pharmacological or therapeutic grouping. The reference pricing system has been adopted by governments as a mechanism to reduce the costs in the public health care system. By setting a price limit, competition among producers has been stimulated.